Answer:
f=4
Step-by-step explanation:
1) first we have to get the "f" by itself. to do this we subtract the 1 from the right side of the equation.
2) and what you do to one side you ALWAYS do to the other side!!! so subtract 1 from the 5 also
3) this leaves you with 4=f
hope this helps!
Answer:
1/9
Step-by-step explanation:
1/3*1/3=1/9
Try photo math it is very helpful
Answer: 1/3 (x + 6)
Explanation: given f(x) = 3x - 6.
Let y = f(x) and so y = 3x - 6.
Trade places between x and y.
x = 3y - 6
Solve for y
x + 6 = 3y
y = x + 6/3
Now the new y is the inverse and so y = f-1(x)
f-1(x) = 1/3(x + 6)